Safety, tolerability, and efficacy of idarucizumab for the reversal of the anticoagulant effect of dabigatran in healthy male volunteers: a randomised, placebo-controlled, double-blind phase 1 trial. Issue 9994 (15th August 2015) - Glund, Stephan; Stangier, Joachim; Schmohl, Michael; Gansser, Dietmar; Norris, Stephen; van Ryn, Joanne; Lang, Benjamin; Ramael, Steven; Moschetti, Viktoria; Gruenenfelder, Fredrik; Reilly, Paul; Kreuzer, Jörg
Summary: Background: Idarucizumab is a monoclonal antibody fragment that binds dabigatran with high affinity in a 1:1 molar ratio. We investigated the safety, tolerability, and efficacy of increasing doses of idarucizumab for the reversal of anticoagulant effects of dabigatran in a two-part phase 1 study (rising-dose assessment and dose-finding, proof-of-concept investigation). Here we present the results of the proof-of-concept part of the study. Methods: In this randomised, placebo-controlled, double-blind, proof-of-concept phase 1 study, we enrolled healthy volunteers (aged 18–45 years) with a body-mass index of 18·5–29·9 kg/m 2 into one of four dose groups at SGS Life Sciences Clinical Research Services, Belgium. Participants were randomly assigned within groups in a 3:1 ratio to idarucizumab or placebo using a pseudorandom number generator and a supplied seed number. Participants and care providers were masked to treatment assignment. All participants received oral dabigatran etexilate 220 mg twice daily for 3 days and a final dose on day 4. Idarucizumab (1 g, 2 g, or 4 g 5-min infusion, or 5 g plus 2·5 g in two 5-min infusions given 1 h apart) was administered about 2 h after the final dabigatran etexilate dose. The primary endpoint was incidence of drug-related adverse events, analysed in all randomly assigned participants who received at least one dose of dabigatran etexilate. Reversal of diluted thrombin time (dTT), ecarin clotting time (ECT), activated partial thromboplastin time (aPTT), and thrombin time (TT) were secondary endpoints assessed by measuring the area under the effect curve from 2 h to 12 h (AUEC2–12 ) after dabigatran etexilate ingestion on days 3 and 4. This trial is registered withClinicalTrials.gov, numberNCT01688830 . Findings: Between Feb 23, and Nov 29, 2013, 47 men completed this part of the study. 12 were enrolled into each of the 1 g, 2 g, or 5 g plus 2·5 g idarucizumab groups (nine to idarucizumab and three to placebo in each group), and 11 were enrolled into the 4 g idarucizumab group (eight to idarucizumab and three to placebo). Drug-related adverse events were all of mild intensity and reported in seven participants: one in the 1 g idarucizumab group (infusion site erythema and hot flushes), one in the 5 g plus 2·5 g idarucizumab group (epistaxis); one receiving placebo (infusion site haematoma), and four during dabigatran etexilate pretreatment (three haematuria and one epistaxis). Idarucizumab immediately and completely reversed dabigatran-induced anticoagulation in a dose-dependent manner; the mean ratio of day 4 AUEC2–12 to day 3 AUEC2–12 for dTT was 1·01 with placebo, 0·26 with 1 g idarucizumab (74% reduction), 0·06 with 2 g idarucizumab (94% reduction), 0·02 with 4 g idarucizumab (98% reduction), and 0·01 with 5 g plus 2·5 g idarucizumab (99% reduction). No serious or severe adverse events were reported, no adverse event led to discontinuation of treatment, and no clinically relevant difference in incidence of adverse events was noted between treatment groups. Interpretation: These phase 1 results show that idarucizumab was associated with immediate, complete, and sustained reversal of dabigatran-induced anticoagulation in healthy men, and was well tolerated with no unexpected or clinically relevant safety concerns, supporting further testing. Further clinical studies are in progress. Funding: Boehringer Ingelheim Pharma GmbH & Co KG.